Land Use Policy Area (LUPA): A Stratagem towards Advanced Preparedness in the ArcGIS Platform - Abante, Ana Marie R.; Abante, Carlo Gabriel R.; Bartolata, Joseph L.; Cobilla, Micael T.; Rosalada, John Patrick R.; Octeza, Francia D.; Torres, Erwin E. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This paper presents a stratagem designed to reduce disaster risk through a Land Use Policy Area (LUPA) geospatial information model for the Municipality of Lupi, Camarines Sur, Philippines. Method – ArcGIS was used to organize data to analyze the distribution of the protection, production, settlement, and infrastructure policy areas for the next ten years planning period aiming to achieve the preferred development strategy of the municipality. Results – The study disclosed that the local government continued protecting 39.37% or 7,988.5 Ha of the land and inland waters of the municipality, properly utilizing the 58.43% or 11,854.6 Ha of land for agricultural uses, using the 1.38% or 279.3 Ha for urban and rural uses, and allocated at least 0.82% or 166.6 Ha of land mostly for transportation use. Focused on the significance of the land-use policies concerning the municipality's plans relative to the need to reduce disaster risk and development constraints, the LUPA geospatial information model for Lupi could fittingly serve as a tool to guide and control its balanced and sustainable growth. As various localities continue to seek answers to the innumerable and diverse challenges posed by climate change, it behooves decision-makers to consider this highly innovative and modern strategy along land-use planning and development to reduce risk and maximize the use of land assets. Conclusion – As the world experiences environmental change, the traditional disaster risk reduction actions are no longer working to resist the changing climate. This necessitates the application of a stratagem crafted to reduce disaster risk through a Land Use Policy Area (LUPA). Using ArcGIS to organize data, the LUPA Geospatial Information Model systematically analyzed data along with the four important policy areas: protection, production, settlement, and infrastructure which shall become the bases of development planning under the strategic development framework of the Municipality of Lupi, Camarines Sur, Philippines. Recommendations – The study highly recommends the adoption of the LUPA Geospatial Information Model focused on the aforesaid four important policy areas to reduce risks and other development constraints as the Municipality of Lupi pursues its priorities and charts its future direction. Practical Implications –As various localities strategize to find solutions to the innumerable challenges posed by climate change, the LUPA for Lupi model can be used to guide land use and local development that strikes physical and environmental balance through continuous monitoring of the municipality’s sustained local development.